The Language Ideology Behind the Screen: Increasing Users’ Awareness of Social Media Disinformation - Talib Muhammadsharif Omer (Zanco Journal of Humanity Sciences)
In recent decades, university students and others have been constantly exposed to information spreading through social media platforms. This information is often false, deliberately misleading people for personal, financial, and political gains. This study aims to assess university students' ability to detect disinformation on social media and raise their awareness of fake news, providing them with relevant fact-checking skills. By examining how students understand and interact with language ideology on social media platforms, this research uncovers implicit beliefs and values influencing the creation and spread of disinformation. It analyzes how linguistic features and communication strategies contribute to false information dissemination. Results from experimental groups showed that students improved their knowledge and enhanced their skills after participating in workshops. The study investigates mechanisms through which language shapes perceptions and influences beliefs, highlighting the need for increased social media literacy and critical thinking to address the disinformation landscape. This study employs a mixed-methods approach, including surveys, pre-tests